Comprehensive profiling of the fission yeast transcription start site activity during stress and media response. Issue 4 (19th December 2018) - Thodberg, Malte; Thieffry, Axel; Bornholdt, Jette; Boyd, Mette; Holmberg, Christian; Azad, Ajuna; Workman, Christopher T; Chen, Yun; Ekwall, Karl; Nielsen, Olaf; Sandelin, Albin
Abstract: Fission yeast, Schizosaccharomyces pombe, is an attractive model organism for transcriptional and chromatin biology research. Such research is contingent on accurate annotation of transcription start sites (TSSs). However, comprehensive genome-wide maps of TSSs and their usage across commonly applied laboratory conditions and treatments for S. pombe are lacking. To this end, we profiled TSS activity genome-wide in S. pombe cultures exposed to heat shock, nitrogen starvation, hydrogen peroxide and two commonly applied media, YES and EMM2, using Cap Analysis of Gene Expression (CAGE). CAGE-based annotation of TSSs is substantially more accurate than existing PomBase annotation; on average, CAGE TSSs fall 50–75 bp downstream of PomBase TSSs and co-localize with nucleosome boundaries. In contrast to higher eukaryotes, dispersed TSS distributions are not common in S. pombe . Our data recapitulate known S. pombe stress expression response patterns and identify stress- and media-responsive alternative TSSs. Notably, alteration of growth medium induces changes of similar magnitude as some stressors. We show a link between nucleosome occupancy and genetic variation, and that the proximal promoter region is genetically diverse between S. pombe strains. Our detailed TSS map constitutes a central resource for S. pombe gene regulation research.